Holding onto lots of hydrogen: a 12-hydride rhodium cluster that reversibly adds two molecules of H2. - Brayshaw, S; Ingleson, M; Green, J; Raithby, P; Kociok-Köhn, G; McIndoe, J; Weller, A (2005)
H Box: The clusters [Rh6(PR3)6H 12][BArF4]2 (R = cyclohexyl, iPr; see scheme, pink Rh, orange P) reversibly take up two molecules of H2 under ambient conditions (1 atm H2, 298 K) to give discrete octahedral clusters surrounded by 16 hydride ligands. (Figure Presented). © 2005 Wiley-VCH Verlag GmbH and Co. KGaA.